Improvement in farm homes - Locke, Bessie May (My University, 1898)
Introduction: Advancement in all lines of work is being made more rapidly at the present time than ever before. In the benefit that comes from modern improvement there is no one who deserves a share more than the farmer. Of course there are great improvements in farm implements, but reference is here made more particularly to the improvement in the farmer’s home and in his family. The house does not need to be a costly affair but it should be arranged and furnished with such taste that the first glimpse would suggest “home.” Houses, especially in the country, are usually planned by a man even though a woman must live in them and work in them much more than man does. It should by all means be planned by a woman. One seldom heard of a woman building a house. If our neighbor builds a house, it is always “Mr. A is having a house built,” never “Mrs. A is having a house built,” but Mrs. A will have to live and work in it, no matter whether it is convenient or not.
Citation: Locke, Bessie May. Improvement in farm homes. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Advancement; Farmer; House; Improvement; Theses; Manuscripts (documents)